A Solution of Second Kind Volterra Integral Equations Using Third Order Non-Polynomial Spline Function (Baghdad Science Journal, 2015)
In this paper, third order non-polynomial spline function is used to solve 2nd kind Volterra integral equations. Numerical examples are presented to illustrate the applications of this method, and to compare the computed results with other known methods.